Faith development of students in schools of the Daughters of Charity in the National Capital Region: a pilot study - Deborde, Lourdes S. (Animo Repository, 1996)
This study describes and analyzes the stages of faith development among students in the schools managed by the Daughters of Charity (DC) in the National Capital Region. Twenty-one students from grade six, senior high school, and college levels were randomly selected from three DC schools in NCR. The students were interviewed using a open-ended, semi-projective format developed from Fowler's Interview Guide. Each interview was taped, transcribed, coded, and scored according to Fowler's criteria for faith stage. This was done by the researcher and two other scorers. The inter-raters agreement yielded an 87 percent reliability. The St. Louis University Non-Verbal Intelligence Test was administered to the grade six and senior high school students while the Purdue Non-Language Test-Form A was given to the college students. The data were subjected to two kinds of analyses. The qualitative analysis detected the structure of interview narratives and coding. Descriptive statistical analysis was applied to determine (1) the significant differences in faith scores between year levels, and (2) the relationship between faith stages and the variables. These were done through an analysis of variance, multiple correlation, and stepwise regression. The qualitative analysis and interpretation of the students' narrative statements revealed that grade six students were at the Transition States 2 and 3 in their faith development. Students at this stage manifested a literal-conventional faith. The senior high school students were at Stage 3 - synthetic-conventional faith. Students at this stage found meaning in life. The preceding confirmed the applicability of Fowler's theory of stages of faith development among Filipino students. The females tended to belong to a higher stage of faith development than the males in grade six and senior high school. Age and mental ability were positively correlated with stages of faith development in grade six and high school. The number of years in the Catholic school was positively related with the stages of faith among grade six and senior high school students. Nurturing of parents was a factor in faith development among the college students. Socio-economic status, and unreflected crisis in life were not related with stages of faith development of students at the three levels. Among the seven variables, age was the best predictor of stages of faith within the age bracket of 12 to 21 years. All these findings are useful in planning and organizing religious education programs and in structuring further research in the area of education and faith. It is recommended that an objective measurement instrument be developed in measuring the faith development of Filipino students.